A Liquid Chromatographic Analysis of Deferasirox in Human Breast Milk with Fluorimetric Detection - Onal, Cem; TEKKELİ, ŞERİFE EVRİM; TEKKELİ, ŞERİFE EVRİM; ASRAM SAĞIROĞLU, ALİ; ASRAM SAĞIROĞLU, ALİ (My University, 2020)
To determine deferasirox in human breast milk a novel, sensitive high-performance liquid chromatographic method with fluorescence detection has been developed. Precolumn derivatization process is applied to achieve fluorescent analyte using 4-bromomethyl-7-methoxy coumarin (BrMmC) as a reagent and dibenzo-18-crown-6-ether as catalyst. The method depends on reverse phase chromatography. C(18)column has been used with 150 x 4.6 mm, 5 mu m particle size and the mobile phase consisting of acetonitrile:phosphate buffer (20 mM, pH 3) (70:30,v/v) with a flow rate of 1.0 mL/min. Fluorescence detection at 390 nm is provided with an excitation at 320 nm The linear range is 0.01-1.0 mu g/mL. The mean recovery has been calculated as 100.7% with a relative standard deviation (RSD) value less than 2%. The developed method was successfully applied for the determination of deferasirox in human breast milk samples.